Whither or Wither the Sulfur Anomaly in Planetary Nebulae? - Shuyu Tan; Quentin A. Parker (The Astrophysical Journal Letters, 2024)
We present a thorough investigation of the long-standing sulfur anomaly enigma. Our analysis uses chemical abundances from the most extensive data set available for 126 planetary nebulae (PNs) with improved accuracy and reduced uncertainties from a 10° × 10° Galactic bulge region. By using argon as a superior PN metallicity indicator, the anomaly is significantly reduced and better constrained. For the first time in PNs we show sulfur α -element lockstep with both oxygen and argon. We dispel hypotheses that the anomaly originates from underestimation of higher sulfur ionization stages. Using a machine-learning approach, we show that earlier ionization correction factor schemes contributed significantly to the anomaly. We find a correlation between the sulfur anomaly and the age/mass of PN progenitors, with the anomaly either absent or significantly reduced in PNs with young progenitors. Despite inherent challenges and uncertainties, we link this to PN dust chemistry, noting those with carbon-dust chemistry show a more pronounced anomaly. By integrating these findings, we provide a plausible explanation for the residual, reduced sulfur anomaly and propose its potential as an indicator of relative galaxy age compositions based on PNs.